Cardio-protective effect of regular transfusion in children with non-transfusion dependent thalassemia (NTDT): A cohort study - Al Senaidi, Khalfan; Maveda, Surekha; Joshi, Niranjan; Nazir , Hanan; Elshinawy, Mohamed; AL Zadjali , Shoaib; Al Rawas , Abdulhakim; Elghamry , Islam; Wali, Yasser; Khater, Doaa (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: Cardiac complications occur in patients with non-transfusion dependent thalassemia (NTDT). The study aimed to evaluate transfusion effect on systolic and diastolic cardiac function in young NTDT patients. Methods: Study design: Cohort study. Seventeen regularly-transfused patients with NTDT (12.5±5.3 years; group 1) and 15 none/minimally transfused patients (13.2±4.8 years; group 2) were followed up for 5 years and compared as regards their clinical parameters, echocardiographic and Tissue-Doppler-Imaging. Results: Group 2 patients had significantly higher peak late-diastolic velocity of the left-ventricular-inflow Doppler (Am). Mitral-valve A-wave duration/pulmonary-veins, A-wave duration-ratio and pulmonary-vein S/D velocities-ratio were larger in group 2 as well (p = < 0.01). The diameters of right and left outflow-tract were larger with a higher cardiac-index in patients of group 2. Systolic-function was similar in the 2 studied groups. Conclusion: Diastolic function assessment revealed indicators of an abnormal relaxation of left-ventricle in non-transfused patients, which suggests a diastolic dysfunction. An increase in the diameter of the outflow-tract is likely attributed to high cardiac-output status in non-transfused NTDT patients as they have a higher cardiac index. Early start of regular transfusion for NTDT patients might prevent serious long-term cardiac complications.